Analisis Hadis Dalam Kitab Hidayatul Muta'allim Karya Sheikh Ahmad Bin Yusuf Al-fatoni - Abdulloh Salaeh; Syed Najihuddin Syed Hassan; Nidzamuddin Zakaria; Amran Abdul Halim; Ahmad Kamel Mohamed (USIM PRESS, 2025)
Journal Of Hadith Studies, Volume 10 issue (1 (SI) Page (88–100)